Identification and mapping of major-effect flowering time loci Autoflower1 and Early1 in Cannabis sativa L. - Toth, Jacob A.; Stack, George M.; Carlson, Craig H.; Smart, Lawrence B. (Frontiers in Plant Science, 2022)
Flowering time is an important trait for all major market classes of hemp (Cannabis sativa), affecting yields and quality of grain, fiber, and cannabinoids. C. sativa is usually considered a short-day plant, flowering once night length reaches a critical threshold. Variations in flowering time within and across cultivars in outdoor grown populations have been previously identified, likely corresponding to genetic differences in this critical night length. Further, some C. sativa are photoperiod insensitive, colloquially referred to as “autoflowering”. This trait has anecdotally been described as a simple recessive trait with major impacts on phenology and yield. In this work, the locus responsible for the “autoflower” trait (Autoflower1), as well as a major-effect flowering time locus, Early1, were mapped using bulked segregant analysis. Breeder-friendly high-throughput molecular marker assays were subsequently developed for both loci. Also detailed are the flowering responses of diverse cultivars grown in continuous light and the result of crossing two photoperiod insensitive cultivars of differing pedigree.